Redes sociales: Análisis de su gestión y eficacia en la comunicación corporativa de las 100 empresas más grandes de Ecuador - Paladines Galarza, F. (2015)
The article presents research on activity in social networks of the 100 largest companies in Ecuador, to emitted invoices and tax contribution; the central object is to analyze the management of corporate communication and measure results, from structured sheets that show quantifiable data. The information is obtained from the profiles and official sites of Facebook, Twitter and You tube. To deepen the analysis, it is taken as reference, a group of 10 companies with increased activity according to the study. Social networking research and the generation of verifiable data with respect to the management of corporate communications, is a pending task in Ecuador. The data correspond to a week of observation (20 to 26 October 2014) of the main accounts of every company. The analyzed aspects are: number of followers, tweets or comments, official postings, number of publications per week and formal digital campaigns, among other parameters. With the above, we pretend to measure the level of interaction between enterprises, their followers and the public response to the information provided by the organizations, as well as the frequency and conditions of use of these communication systems.